Electrochemically synthesized faceted CuInTe2 nanorods as an electron source for field emission applications - Lakhe, Manorama G.; Joshi, Padmshree; Choudhary, Ram J.; Ganesan, V.; Joag, Dilip S.; Chaure, Nandu B. (New Journal of Chemistry, 2018)
Herein, CuInTe2 (CIT) thin films with faceted nanorod-like morphology have been synthesized on a flexible molybdenum foil using a water-based low-cost electrodeposition technique. The co-deposition potential for CIT was optimized using cyclic voltammetry with respect to that of the Ag/AgCl reference electrode, and films were deposited from -0.6 V to -0.9 V at the working temperature of 75 degrees C. The as-prepared CIT films exhibited an amorphous nature, whereas the RTP-annealed films exhibited a highly crystalline chalcopyrite nature as a function of the growth potential. A red shift was observed in the Raman spectra of the as-deposited films that shifted towards the original position upon annealing. The Cu/In ratio obtained by the EDS analysis was found to decrease systematically upon increasing the growth potential. X-ray photoelectron spectroscopy (XPS) studies revealed the presence of Cu+, Cu2+ satellites, In3+, Te2-, and Te4+ states of Cu, In, and Te. The field emission study showed a maximum current density of 1.74 mA cm(-2), which was attainable at an applied electric field of 1.5 V mu m(-1). The turn-on field was found to be 0.92 V mu m(-1), comparable to that of the carbon nanofibres. The emitter exhibited stable electron emission over a period of 3 hours. The faceted CIT nanorods with columnar growth are a potential candidate for application as an electron source, and herein, the field emission of CIT nanorods is reported for the first time.

Transport properties of cuinte2 thin films obtained by the electrochemical route - Lakhe, Manorama G.; Chaure, Nandu B. (Journal of electronic materials, 2018)
uInTe2 (CIT) thin films were potentiostatically electrodeposited onto cadmium sulfide thin films coated on fluorine doped tin oxide (FTO) glass in an aqueous bath at 75 degrees C by the standard three-electrode system at -0.7 V and -0.8 V, with respect to an Ag/AgCl reference electrode. The electrodeposited layers were heat treated at similar to 80 degrees C in air ambient for 60 min. X-ray diffraction pattern and Raman analysis confirmed the formation of chalcopyrite CIT thin films upon heat treatment. The optical band gap of heat treated CIT films was found to be similar to 1.0 eV and 0.95 eV deposited at -0.7 V and -0.8 V, respectively. Compact and good adhesive growth of CIT layers onto CdS coated FTO substrates is confirmed by field emission scanning electron microscopy. The current density-voltage (J-V) and capacitance-voltage (C-V) measurement was studied to understand the electronic quality of material for development of CIT layers for solar cell applications. The current density was found to be increased by two orders of magnitude upon low-temperature heat treatment. The capacitance-voltage measurement showed sharp depletion and accumulation region. The built in potential was found to be similar to 60 mV and 145 mV in the as-deposited samples, deposited at -0.7 V and -0.8 V, respectively, whereas upon heat treatment it shifted to 159 mV and 210 mV. The capacitance of the CIT films was found to be a function of applied bias and increased with increasing the bias voltage. The depletion width of the heat treated sample was found to be similar to 20 nm and 200 nm for the sample deposited at -0.7 V and -0.8 V, respectively. Thus, the sample deposited at -0.8 V shows optimum electronic properties and is found to be suitable for opto-electronic applications.

Growth of Mo-doped Ni3S2 nanorods array for superior overall water splitting reaction - Sharma, Pooja; Khandare, Lina; Saha, Arindam; Chaure, Nandu B.; Yengantiwar, Ashish (International Journal of Hydrogen Energy, 2025)
Designing novel, efficient and cost-effective dual-functional electrocatalyst for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) using an alkaline electrolyte is crucial for establishing a sustainable hydrogen economy and transitioning to a society powered by renewable energy sources. In the present work, Mo-doped nickel sulfide (Mo-Ni3S2) nanorods were grown on Ni-treated nickel foam (N-NF) substrate via a two-steps hydrothermal method. Specifically, Mo-Ni3S2/N-NF surface consists of nanorods-like morphology, which provides extensive area for percolation of electrolyte, that resulting in outstanding catalytic performance. Such a well-synthesized electrode exhibited superior performance and stability for OER as compared with pristine Ni3S2/NF and bare nickel foam (NF) electrodes. In addition, Mo-Ni3S2/N-NF electrode provides good HER activity and confirms its dual-functionality in alkaline medium. Our champion Mo-Ni3S2/N-NF electrocatalyst delivers best OER overpotential of 230 mV at current density of 100 mA/cm(2). Also, it provides HER overpotential of 100.6 mV at a current density of 10 mA/cm(2). Both OER and HER are carried out in the presence of 1 M KOH alkaline electrolyte. OER stability of the best-performed Mo-Ni3S2/N-NF electrode demonstrates almost constant current density similar to 120 mA/cm(2), which retains 90% of original value after continuously tested for the duration of 22 h. The total cell voltage of 1.56 V is provided by Mo-Ni3S2/N-NF integrated system and it demonstrates a good stability for duration of 22 h. Our approach provides a new insight into developing earth-abundant, inexpensive and superior dual-functional electrocatalyst for overall water splitting reaction (WSR).
Keywords: Dual-functional electrocatalyst; HER; Mo doping; Nickel sulfide nanorods; OER; overall water splitting